DEVELOPMENT OF A NITROCELLULOSE MEMBRANE-BASED TEST STRIP FOR DETECTING MERCURY (II) - Dyah Wulandari, Devyana; Muhammad Fadillah, Farchan; Ulan Sari, Della Citra; Mufida, Nisaul; Wilujeng, Putri Shinta (Walisongo Journal of Chemistry, 2025)
Mercury (Hg), a hazardous heavy metal, has become a significant environmental and public health concern. Practical tools for detecting mercury in water and cosmetic samples remain limited. This study aimed to develop a nitrocellulose membrane–based test strip capable of detecting mercury through its reaction with diphenylcarbazide. The development process involved the formation of a purple-colored complex resulting from the interaction between mercury ions and diphenylcarbazide, which served as the visual indicator of mercury presence. The selectivity of the test strip was evaluated against non-mercury ions, and its accuracy (%) was compared to the atomic absorption spectroscopy (AAS) method. The results revealed that the nitrocellulose membrane–based test strip was selective toward mercury ions, exhibited a clear color response with increasing mercury concentrations, and demonstrated a relatively high accuracy of 83.33%. These findings suggest that the developed test strip has strong potential as a semi-quantitative and portable tool for mercury detection.